Recent applications of microextraction sample preparation techniques in biological samples analysis - Daryanavard, Seyed Mosayeb; Zolfaghari, Hesane; Abdel‐Rehim, Abbi; Abdel‐Rehim, Mohamed (Biomedical chromatography, 2021)
Analysis of biological samples is affected by interfering substances with chemical properties similar to those of the target analytes, such as drugs. Biological samples such as whole blood, plasma, serum, urine and saliva must be properly processed for separation, purification, enrichment and chemical modification to meet the requirements of the analytical instruments. This causes the sample preparation stage to be of undeniable importance in the analysis of such samples through methods such as microextraction techniques. The scope of this review will cover a comprehensive summary of available literature data on microextraction techniques playing a key role for analytical purposes, methods of their implementation in common biological samples, and finally, the most recent examples of application of microextraction techniques in preconcentration of analytes from urine, blood and saliva samples. The objectives and merits of each microextration technique are carefully described in detail with respect to the nature of the biological samples. This review presents the most recent and innovative work published on microextraction application in common biological samples, mostly focused on original studies reported from 2017 to date. The main sections of this review comprise an introduction to the microextraction techniques supported by recent application studies involving quantitative and qualitative results and summaries of the most significant, recently published applications of microextracion methods in biological samples. This article considers recent applications of several microextraction techniques in the field of sample preparation for biological samples including urine, blood and saliva, with consideration for extraction techniques, sample preparation and instrumental detection systems.